2017
DOI: 10.24998/maeusabed.298679
|View full text |Cite
|
Sign up to set email alerts
|

Bir Devlet Hastanesinin Yoğun Bakım Ünitelerinde İnvaziv Araç Kullanımı ve Enfeksiyon

Abstract: There have been many invasive interventions on the patients in intensive care units. The applied invasive intervention, the medication used and the duration of staying affect the liability to cross (nosocomial) infection. It was aimed in this study to present the current situation of Burdur State Hospital by comparing the surveillance data related to invasive device from the patients monitored at intensive care units of the hospital to the national data and other studies. In the study, infections related to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Kara ve ark. (24) (2015) çalışmasında hemşirelerin TYD bilgisinin sosyodemografik değişkenlerden ziyade TYD eğitimlerine katılma durumuyla ilişkili olduğunu bildirmiştir. Sağlık kurumlarında görev alan hemşirelere verilecek TYD eğitimlerinin sayısının ve niteliğinin arttırılması gerektiğine, hemşirelerin rastladıkları vakaları kolay tanıyabilmelerini ve uygun tedavi yapılabilmesine olanak sağlayacağına dikkat çekmiştir.…”
Section: Discussionunclassified
“…Kara ve ark. (24) (2015) çalışmasında hemşirelerin TYD bilgisinin sosyodemografik değişkenlerden ziyade TYD eğitimlerine katılma durumuyla ilişkili olduğunu bildirmiştir. Sağlık kurumlarında görev alan hemşirelere verilecek TYD eğitimlerinin sayısının ve niteliğinin arttırılması gerektiğine, hemşirelerin rastladıkları vakaları kolay tanıyabilmelerini ve uygun tedavi yapılabilmesine olanak sağlayacağına dikkat çekmiştir.…”
Section: Discussionunclassified
“…Increased resistance to antibiotics, the emergence and spread of antimicrobial resistance in intensive care units are considered as global public health threats today (5). Patients treated in intensive care units (ICUs) make up 5-10% of hospitalized patients, and 25% of hospital infections are seen in ICUs (6). In recent years, according to the studies conducted on hospital infections and risk factors in Turkey, it has been reported that the rate of hospital infections is between 3.1% and 14.1%, and the places where hospital infections are seen the most are in ICUs (7,8).…”
Section: Introductionmentioning
confidence: 99%